Smart Hotel Security: Integrating AI for Advanced Safety Solutions - Djauhari, Teuku; Rahmawati, Noni (Internet of Things and Artificial Intelligence Journal, 2025)
Security systems are essential for hotels and lodging services, considering that this lodging service is a service that is intended for all people from various circles and from anyone who comes from various places, this is very common and dangerous, in terms of security and comfort. Several security systems are built by hotels, such as CCTV and security systems on doors and various security system techniques such as retina, fingerprint, RFID, and various security techniques. Not only at the door but safety boxes are made with various locking techniques from a combination of numbers. In addition to hardware, software with enhanced capabilities in Artificial Intelligence can also be applied such as face detection, predictive analysis, and automated surveillance. The combination of hardware such as Jetson Nano and software can be improved to build AI-based security systems in creating security systems in hotels that can be built professionally and smartly. Some methods developed in the face detection system of a person trying to enter a hotel room to commit theft, for example, are using Convolutional Neural Network (CNN). The developed system can detect predictions of age, gender, and other parameters.